Evaluation of a trastuzumab-containing treatment regimen for patients with unresectable advanced or recurrent gastric cancer - NAMIKAWA, TSUTOMU (Mol Clin Oncol, 2016)
The present study aimed to evaluate the efficacy and safety of trastuzumab plus chemotherapy for patients with unresectable advanced or recurrent gastric cancer. A retrospective analysis of 213 patients with unresectable advanced or recurrent gastric cancer who received systemic chemotherapy, including 15 patients who were also administered trastuzumab, at Kochi Medical School between 2007 and 2013 was performed. The overall survival was compared between patients who received trastuzumab plus chemotherapy and patients who received chemotherapy alone, and the safety and efficacy of the trastuzumab-containing regimen was evaluated. Human epidermal growth factor receptor (HER)2 status was examined in 86 patients, of whom 15 (17.4%) exhibited strong positive HER2 expression. The rate of strong positive HER2 expression was significantly higher for intestinal type tumors compared with diffuse type tumors [23.6 (13/55) vs. 6.5% (2/31); P=0.044]. The median overall survival of the patients treated with trastuzumab was significantly longer compared with that for patients who were not treated with trastuzumab (22.9 vs. 11.6 months; P=0.014). The objective response rate and disease control rate for trastuzumab plus chemotherapy were 46.7 and 86.7%, respectively. Frequently encountered grade 3–4 toxicities included neutropenia (26.7%; 4/15), anemia (13.3%; 2/15) and fatigue (13.3%; 2/15). Trastuzumab plus chemotherapy is effective for patients with HER2-positive advanced or recurrent gastric cancer, and the frequencies of hematological and non-hematological toxicities experienced by patients in the present study indicated that it can be safely administered clinically.